(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-3-167-175 The aim of this research is to describe the functions and the place of professional teaching communication in the process of creating professional competence of the future specialists - teachers of the foreign languages. The relevance of this research is to show the main forms of teaching and educational activities which are a part of pedagogical communication. It also aims to identify the role of teaching practice in this process. Observations of psycho-pedagogical literature and scientific works on the competences of professors in the field of professional-pedagogical communication allows to identify the following: 1) professional-pedagogical facilities of the professor are assessed by the levels of the formed competences of the specialist with the implementation of the competence approach; 2) the culture of communication of the teacher is considered as a necessary part of pedagogical communication, and at the same time as an index of effective learning and creating comfortable conditions both for teachers and students. Peculiarities of teaching, that involves pedagogical communication skills, are not stated in the state standard of higher education. During teaching practice, students have an opportunity to obtain communication competence. The results show that the preparation of the teacher of the foreign languages to of professional-pedagogical communication is the main thing of effective teaching process. Obtaining professional lexemes, future teachers are on their way to form future professionals, and they get ready to use foreign speech while working. It helps to build a rapport between the teacher and the students. While obtaining terms of Lingua didactics and speech patterns of pedagogical influence that are suitable to methodological situations and their implementation in the teaching process helps to form communicative norms in the speech of teachersto-be. Key words: teacher, foreign language, pedagogical communication, specialist training, professional competence, competence approach, communicative culture